Assessment of off-shore wind farms in Malaysia - Mekhilef, Saad; Chandrasegaran, D. (2011)
A lot of attention is being paid to wind energy due to the focus on renewable energy. Malaysia is situated in the equatorial region and its climate is governed by the monsoons. Wind resource in Malaysia varies from one location to another. Wind speed is better offshore compared to onshore, so more contribution by offshore wind powers in terms of electricity generation. Wind energy potentiality and techno- economic feasibility of offshore wind farms in Malaysia is investigated in this paper. Research was conducted using HOMER software to assess the potential of wind energy along the South China Sea coastline. This study indicates the best sites to set up offshore wind farms in Malaysia while costs associated for wind energy generation are calculated. Two model of the wind turbines Vestas V-47 and V-80 are taken for economic feasibility analyses. Investment, operation and maintenance costs have been evaluated for offshore wind energy. Feed-in tariff policy effects energy price and wind farms profitability were analyzed.